Anton Martin Slomšek, Djanje svetnikov božjih – vzgoja duha, kultura srca in govora v novoslovenskem knjižnem jeziku sredi 19. stoletja - Orožen, Martina (Slavia Centralis, 2020)
Anton Martin Slomšek, Djanja svetnikov božjih – The Education of the Spirit, the Culture of the Heart and Speech in the Neo- Slovene Literary Language of the Middle of the 19th Century This article analyzes in detail Slomšek’s extensive publication of Saints’ biographies Djanja Svetnikov božjih, published in 1853–1854 in Graz. This publication is of great importance to Slovene literature because it promotes the culture of spirit (ethical standards), culture of heart (nobleness of action) and the linguistic, written and spoken culture of expression. The text successfully initiated a normatively unified, common, new-Slovene literary language in the 19th century which was further developed through the efforts of linguistic theoreticians and practitioners.